Enhancement of Voltage Stability by Optimal Placement of Shunt Compensation using Bus Voltage Stability Indices and Reactive Power Margin - Devkota, Madhav; Adhikari, Sujan (Himalayan Journal of Applied Science and Engineering, 2022)
Voltage stability problem has caused several blackouts in many countries in recent years. Impending voltage instability has been a significant threat to modern power system’s security and reliability. Moreover, the operation and planning of large interconnected power systems is becoming increasingly complex as power demand rises, posing a security risk to the grid. Appropriate efforts to improve power system security and increase voltage stability margin should be planned to keep the system secure. This work investigates the voltage stability of a power system with and without a shunt capacitor. The bus voltage stability index, L index, is used to measure the distance of the power system to its stability limit in order to assign the shunt capacitor. The L-index for a particular load state is computed for all load buses, and the greatest L-index indicates the system’s approach to voltage collapse. The system’s load ability margin is being traced utilizing a static voltage stability evaluation approach, i.e., PV and QV curve analysis. The minimal power loss approach is used to calculate the optimal capacitor size. The effect of shunt compensation was simulated, and the results with and without compensation were compared. The IEEE-9 bus system was employed in this work, and the system was simulated using MATLAB and Power World Simulator. The result demonstrates that the shunt capacitor enhances voltage stability by injecting the appropriate reactive power.